Slurry of high-nickel positive electrode active material as well as preparation method and application of slurry

By adding antioxidants and halosilane to the slurry of high nickel positive electrode active material, combined with specific slurry composition and preparation methods, the problem of slurry gelation is solved and efficient battery capacity performance is achieved.

CN119400868AActive Publication Date: 2025-02-07SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411519605.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The slurry of high-nickel positive electrode active material is prone to gelation, resulting in reduced processing performance and inability to coat normally, and existing solutions such as water washing and oxalic acid neutralization will lead to a decrease in battery capacity.

Method used

The slurry including high-nickel positive electrode active materials, antioxidants, halogenated silanes, polyvinylidene fluoride and conductive agents is used to inhibit the cross-linking reaction of polyvinylidene fluoride and prevent gelation through specific mixing and preparation methods.

Benefits of technology

The fluidity and stability of the slurry of high-nickel positive electrode active material is achieved, the gelation phenomenon is avoided, and the excellent capacity performance of the battery is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400868A_ABST
    Figure CN119400868A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to slurry of a high-nickel positive electrode active material as well as a preparation method and application of the slurry. Wherein the slurry comprises a solid component and a solvent, and based on the total mass of the solid component, the slurry comprises the following components in percentage by mass: 94%-98.5% of a high-nickel positive electrode active material; 0.005% to 0.5% of an antioxidant; 0.01% to 0.5% of halogenated silane; 1%-2% of polyvinylidene fluoride; 0.5%-3% of a conductive agent; the slurry of the high-nickel positive electrode active material can inhibit gelation of the slurry, and meanwhile, a battery containing the slurry has relatively high capacity performance and has excellent performance when being applied to electric equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials, and specifically relates to a slurry of high-nickel positive electrode active material and a preparation method and application thereof. Background Art

[0002] Lithium nickel cobalt manganese oxide material (transition metal elements include Ni, Co, and Mn, referred to as ternary material) is one of the most commonly used positive electrode materials for high-energy-density power batteries. The higher the proportion of Ni element, the more electrons can participate in the electrochemical reaction, the higher the gram capacity of the ternary material, and the greater the energy density.

[0003] However, as the nickel content increases (especially high-nickel ternary materials with a nickel content greater than 60%), the content of lithium salts remaining on the surface of the material increases, resulting in an increase in residual alkali on the surface. For example, the residual alkali content of NCM811 is about 5.5 times that of NCM622. Such a high residual alkali content causes the processing performance of the high-nickel ternary material to drop sharply. That is, during use, over time, the viscosity of the high-nickel ternary slurry increases rapidly, loses fluidity, and cannot be coated. This phenomenon is called "gelation" or "jellyization" of the high-nickel ternary slurry.

[0004] Because high-nickel cathode materials cannot come into contact with water, water cannot be selected as a solvent during homogenization, which makes water-soluble binders unusable. Generally, organic solvents such as N-methylpyrrolidone (NMP) are selected as solvents for homogenization of cathode materials. Polyvinylidene fluoride (PVDF) has good solubility in the above organic solvents, stable chemical properties, and strong bonding ability. It is currently almost the only choice for cathode material binders in the industry.

[0005] The fundamental reason for the gelation of high-nickel ternary slurry is that the base (residual alkali on the surface of high-nickel ternary or amine group in NMP) attacks the CH and CF of polyvinylidene fluoride to produce elimination reaction, forming C=C double bond to produce chemical crosslinking. Due to the high regularity of polyvinylidene fluoride chain, continuous HF removal reaction is prone to occur, and then cross-linking polymerization reaction occurs, which eventually leads to slurry gelation.

[0006] At present, the solutions to the above problems include (1) water washing to reduce the residual alkali content of high-nickel ternary materials; (2) adding oxalic acid to the slurry to neutralize the residual alkali. However, although water washing of the material can wash away most of the residual alkali, it will be accompanied by a decrease in capacity; and the reaction of oxalic acid neutralizing the residual alkali will generate water, which will cause side reactions between the water and the electrolyte and the negative electrode interface, reducing the battery capacity. Summary of the invention

[0007] Therefore, the technical problem to be solved by the present invention is to overcome the defect in the prior art that inhibiting the gelation of high-nickel positive electrode active material slurry will lead to a decrease in battery capacity, thereby providing a slurry of high-nickel positive electrode active material and its preparation method and application.

[0008] To this end, the present invention provides the following technical solutions:

[0009] The first aspect of the present invention protects a slurry of a high-nickel positive electrode active material, wherein the slurry comprises a solid component and a solvent, and comprises the following components in percentage by weight based on the total weight of the solid component:

[0010] High nickel positive electrode active material 94%-98.5%;

[0011] Antioxidants 0.005%-0.5%;

[0012] Halogenated silane 0.01%-0.5%;

[0013] Polyvinylidene fluoride 1%-2%;

[0014] Conductive agent 0.5%-3%.

[0015] According to the present invention, the antioxidant includes at least one of butylated p-hydroxyanisole (BHA), 2,6-di-tert-butylated p-quinone (BHT), propyl gallate (PG), tert-butylhydroquinone, and benzoquinone, and can be tert-butylated p-hydroxyanisole and / or 2,6-di-tert-butylated p-quinone.

[0016] In the present invention, the antioxidant mechanism is taken as an example of BHT, specifically:

[0017]

[0018] According to the present invention, the halogenated silane includes silicon tetrachloride and / or hexachlorodisilane.

[0019] In the present invention, the specific reaction formula of silicon tetrachloride is:

[0020] SiCl4+H2O→H4SiO4+H2SiO3+HCl;

[0021] SiCl4+LiOH→SiO2+HCl+LiCl.

[0022] According to the present invention, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, and graphene.

[0023] According to the present invention, the conductive agent includes a first conductive agent and a second conductive agent;

[0024] The first conductive agent includes at least one of conductive carbon black, conductive graphite, and carbon fiber;

[0025] The second conductive agent includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.

[0026] According to the present invention, based on the total solid mass percentage in the slurry of the high-nickel cathode active material, the dosage of the first conductive agent is 1% - 2%, and the dosage of the second conductive agent is 0.2% - 0.8%.

[0027] In the present invention, the nickel content of the high-nickel cathode active material of the cathode material is above 70%; the high-nickel cathode active material includes at least one of a high-nickel ternary cathode material, a cobalt-free cathode material, and a quaternary cathode material; the composition of the high-nickel ternary cathode material is LiNi x Co y Mn 1-x-y O2, where 0.7 ≤ x < 1, 0 < y ≤ 0.3, 0 < x + y < 1; the composition of the cobalt-free cathode material is LiNi x Mn 1-x O2, where 0.7 ≤ x < 1; the composition of the quaternary cathode material is LiNi x Co y Mn z Al 1-x-y-z O2, where 0 < x + y + z < 1.

[0028] According to the present invention, the number-average molecular weight of the polyvinylidene fluoride is 500,000 - 1,500,000.

[0029] According to the present invention, the mass ratio of the solvent to the polyvinylidene fluoride is (90 - 100):(1 - 10).

[0030] According to the present invention, the solvent includes at least one of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), and dimethyl sulfoxide (DMSO), and preferably N-methylpyrrolidone.

[0031] The second aspect of the present invention protects a method for preparing the aforementioned slurry, wherein a slurry of the high-nickel cathode active material is obtained by mixing the high-nickel cathode active material, an antioxidant, a halogenated silane, polyvinylidene fluoride, and a conductive agent.

[0032] According to the present invention, the preparation method includes the following steps:

[0033] S1, perform a first mixing of the polyvinylidene fluoride and the solvent to obtain a colloidal solution;

[0034] S2, perform a second mixing of the above colloidal solution, the conductive agent, and the high-nickel cathode active material to obtain a mixture;

[0035] S3, add an antioxidant and silicon tetrachloride to the mixture for a third mixing to obtain a slurry of the high-nickel cathode active material.

[0036] In the present invention, the preparation of the colloidal solution is carried out in a colloidal solution preparation machine.

[0037] According to the present invention, in step S2, the first conductive agent is mixed with the glue solution to obtain conductive glue A, and the second conductive agent is added and mixed to obtain conductive glue B; and the conductive glue is then mixed with the high-nickel positive electrode active material to obtain a mixture.

[0038] In the present invention, the conditions for the first mixing, the second mixing, and the third mixing are conventional conditions in the art, and they only need to be mixed uniformly.

[0039] A third aspect of the present invention provides a secondary battery, wherein the battery comprises the slurry of the aforementioned high-nickel positive electrode active material.

[0040] In the present invention, the preparation method of the battery is a conventional method in the art. Typically, but not limitedly, the prepared positive electrode slurry containing high nickel positive electrode active material is evenly coated on the current collector aluminum foil, and the coating amount is 12-14 mg / cm 2 , then drying at 85-90°C, cold pressing, trimming, cutting, slitting, drying at 85-90°C under vacuum conditions for 3-4h, welding the tabs, and making a positive electrode sheet for a lithium-ion secondary battery that meets the requirements;

[0041] The negative electrode active material artificial graphite, conductive agent Super-P, thickener CMC, and adhesive SBR are dissolved in deionized water in a mass ratio of (96-98): (1.0-1.1): (1.0-1.1): (1.2-1.5) and mixed evenly to form a negative electrode slurry, and the negative electrode slurry is evenly coated on the current collector copper foil with a coating amount of 8-9 mg / cm 2 , then dried at 85-90°C, cold pressed, trimmed, cut into pieces, and slit, and then dried at 110-120°C under vacuum conditions for 3-4 hours, and the tabs are welded to produce a negative electrode sheet for a lithium-ion secondary battery that meets the requirements;

[0042] The electrolyte, positive electrode sheet, negative electrode sheet and isolation film (PE film) obtained in the examples and comparative examples were laminated to form a battery with a thickness of 8 mm, a width of 60 mm and a length of 130 mm, and then vacuum-baked at 85°C for 10 h, injected with electrolyte and left to stand for 24 h.

[0043] A fourth aspect of the present invention protects an electrical device, which includes the aforementioned secondary battery.

[0044] The technical solution of the present invention has the following advantages:

[0045] The present invention provides a slurry of a high-nickel positive electrode active material, wherein the slurry comprises a solid component and a solvent, and comprises the following components in percentage by weight based on the total weight of the solid component: 94%-98.5% of a high-nickel positive electrode active material; 0.005%-0.5% of an antioxidant; 0.01%-0.5% of a halogenated silane; 1%-2% of polyvinylidene fluoride; and 0.5%-3% of a conductive agent. The slurry of the high-nickel positive electrode active material of the present invention does not undergo a gelation phenomenon, wherein during the use of the high-nickel ternary positive electrode material, residual bases on the surface of the polyvinylidene fluoride attack the polyvinylidene fluoride, causing a polymerization reaction of the polyvinylidene fluoride, and the antioxidant of the present invention can inhibit the removal of H + With F - The polyvinylidene fluoride undergoes a cross-linking reaction to form a gel; while silicon tetrachloride will react with the positive electrode material to generate water and residual alkali. Compared with oxalic acid, silicon tetrachloride will not produce side reactions, and silicon tetrachloride is inexpensive, has high reaction activity, and has a fast reaction speed, so that the battery containing the slurry of the high-nickel positive electrode active material of the present invention will not produce gelation of the slurry and maintain excellent capacity performance.

[0046] In the present invention, when the antioxidant is tert-butyl-p-hydroxyanisole and 2,6-di-tert-butyl-p-benzophenol, the flow characteristics of the slurry can be further improved and the capacity of the battery can be increased.

[0047] The present invention limits the types of the first conductive agent and the second conductive agent, which can further improve the flow characteristics of the slurry and increase the capacity of the high-nickel positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 The slurry of high nickel positive electrode active material prepared in Example 1;

[0050] Figure 2 Comparative Example 2: Slurry of high nickel positive electrode active material prepared. DETAILED DESCRIPTION

[0051] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0052] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0053] Example 1

[0054] This embodiment provides a slurry of a high-nickel positive electrode active material. Based on the total solid mass percentage in the slurry of the high-nickel positive electrode active material, polyvinylidene fluoride is 1.2%, conductive carbon black is 1%, single-walled carbon nanotubes are 0.5%, and cobalt-free high-nickel positive electrode active material (LiNi 0.75 Mn 0.25 O2) is 97.1%, 2,6-di-tert-butyl-p-benzophenol is 0.1%, silicon tetrachloride is 0.1%; the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 93:7;

[0055] The method for preparing the slurry of the high nickel positive electrode active material is specifically as follows:

[0056] S1, adding N-methylpyrrolidone and polyvinylidene fluoride into a glue making machine, performing a first mixing to obtain a glue solution;

[0057] S2, adding the above glue and conductive carbon black into the glue to mix, to obtain conductive glue A; adding single-walled carbon nanotubes into conductive glue A to mix, to obtain conductive glue B; and mixing conductive glue B with cobalt-free high-nickel positive electrode active material LiNi 0.75 Mn 0.25 O2 is mixed to obtain a mixture;

[0058] S3, mixing the mixture with silicon tetrachloride and 2,6-di-tert-butyl-p-benzophenol to obtain a slurry of high-nickel positive electrode active material;

[0059] The high nickel positive electrode active material prepared in Example 1 is as follows Figure 1 As shown, from Figure 1 It can be seen that the slurry of the high nickel positive electrode active material prepared in Example 1 can flow freely and be coated smoothly.

[0060] Example 2

[0061] This embodiment provides a slurry of a high-nickel positive electrode active material. Based on the total solid mass percentage in the slurry of the high-nickel positive electrode active material, polyvinylidene fluoride is 1.2%, conductive carbon black is 1%, single-walled carbon nanotubes are 0.5%, and the high-nickel ternary high-nickel positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1O2) is 97.1%, 2,6-di-tert-butyl-p-benzophenol is 0.1%, silicon tetrachloride is 0.1%; the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 93:7;

[0062] The method for preparing the slurry of the high nickel positive electrode active material is specifically as follows:

[0063] The method of Example 1 is followed, except that different amounts are used.

[0064] Example 3

[0065] This embodiment provides a slurry of a high-nickel positive electrode active material. Compared with Embodiment 1, the difference is that an equal mass of tert-butyl-p-hydroxyanisole is used instead of 2,6-di-tert-butyl-p-quinoline.

[0066] Example 4

[0067] The present embodiment provides a slurry of a high-nickel positive electrode active material. Compared with Example 1, the difference is that 2,6-di-tert-butyl-p-quinol and tert-butyl-p-hydroxyanisole (wherein the total mass of 2,6-di-tert-butyl-p-quinol and tert-butyl-p-hydroxyanisole is equal to the mass of 2,6-di-tert-butyl-p-quinol in Example 1, and the mass ratio of 2,6-di-tert-butyl-p-quinol and tert-butyl-p-hydroxyanisole is 1:1) is used instead of 2,6-di-tert-butyl-p-quinol.

[0068] Example 5

[0069] This embodiment provides a slurry of a high-nickel positive electrode active material. Compared with Embodiment 1, the difference is that an equal mass of benzoquinone is used instead of 2,6-di-tert-butyl-p-benzophenol.

[0070] Example 6

[0071] This embodiment provides a slurry of a high-nickel positive electrode active material, in which, based on the total solid mass percentage in the slurry of the high-nickel positive electrode active material, polyvinylidene fluoride is 1.2%, conductive carbon black is 1.5%, cobalt-free high-nickel positive electrode active material is 97.2%, 2,6-di-tert-butyl-p-quinone is 0.1%, and silicon tetrachloride is 0.1%; the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 93:7;

[0072] The method for preparing the slurry of the high nickel positive electrode active material is specifically as follows:

[0073] S1, proceed according to step S1 of embodiment 1;

[0074] S2, adding conductive carbon black to the above glue solution and mixing them to obtain conductive glue; mixing the conductive glue with cobalt-free high-nickel positive electrode active material LiNi 0.75 Mn 0.25 O2 is mixed to obtain a mixture;

[0075] S3, proceed according to step S3 of Example 1.

[0076] Example 7

[0077] This embodiment provides a slurry of a high-nickel positive electrode active material. Based on the total solid mass percentage in the slurry of the high-nickel positive electrode active material, polyvinylidene fluoride is 1.8%, conductive carbon black is 1.5%, single-walled carbon nanotubes are 0.3%, and the high-nickel ternary high-nickel positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 O2) is 96.2%, 2,6-di-tert-butyl-p-benzophenol is 0.1%, silicon tetrachloride is 0.1%; the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 93:7;

[0078] The method for preparing the slurry of the high nickel positive electrode active material is specifically as follows:

[0079] The method of Example 1 is followed, except that different amounts are used.

[0080] Comparative Example 1

[0081] The difference between this comparative example and Example 1 is that 0.1% of silicon tetrachloride is removed from the solid in the slurry, the content of the positive electrode active material is increased by 0.1% to 97.2%, and the types and amounts of other components remain unchanged;

[0082] The method for preparing the slurry of the high nickel positive electrode active material is specifically as follows:

[0083] The process is carried out in the manner of Example 1, except that, in step S3, silicon tetrachloride is not added.

[0084] Comparative Example 2

[0085] The difference between this comparative example and Example 1 is that 0.1% of 2,6-di-tert-butyl-p-benzophenol is removed from the solid in the slurry, the content of the positive electrode active material is increased by 0.1% to 97.2%, and the types and amounts of other components remain unchanged;

[0086] The method for preparing the slurry of the high nickel positive electrode active material is specifically as follows:

[0087] The process is carried out in the manner of Example 1, except that, in step S3, 2,6-di-tert-butyl-p-benzophenol is not added.

[0088] The material obtained in Comparative Example 2 is as follows Figure 2 As shown in the figure, it can be seen that the slurry is in a solidified state and severe gelation occurs, making it impossible to apply normally.

[0089] Comparative Example 3

[0090] This comparative example provides a slurry of a high-nickel positive electrode active material. Compared with Example 1, the difference is that an equal mass of oxalic acid is used instead of silicon tetrachloride.

[0091] Test Case

[0092] (1) The slurries prepared in the examples and comparative examples were placed in air for 2 h to detect the fluidity. The fluidity of different slurries was tested by a rheometer at the same shear rate (0.1 / s -1 ), the specific results are shown in Table 1.

[0093] Table 1

[0094] Shear viscosity (Pa s) Example 1 1020 Example 2 1080 Example 3 1010 Example 4 980 Example 5 1400 Example 6 1500 Example 7 1060 Comparative Example 1 6000(mild gel) Comparative Example 2 5800(mild gel) Comparative Example 3 2000

[0095] (2) The prepared positive electrode slurry containing high nickel positive electrode active material is evenly coated on the current collector aluminum foil, with a coating amount of 13.8 mg / cm 2 , then dried at 85°C, cold pressed, trimmed, cut into pieces, and slit, and then dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to produce a positive electrode sheet for a lithium-ion secondary battery that meets the requirements;

[0096] The negative electrode active material artificial graphite, conductive agent Super-P, thickener CMC, and binder SBR were dissolved in deionized water at a mass ratio of 96.5:1.0:1.0:1.5 and mixed evenly to form a negative electrode slurry. The negative electrode slurry was evenly coated on the current collector copper foil with a coating amount of 8.3 mg / cm 2 , then dried at 85°C, cold pressed, trimmed, cut into pieces, and slit, and then dried at 110°C under vacuum conditions for 4 hours, and the tabs were welded to produce a negative electrode sheet for a lithium-ion secondary battery that meets the requirements;

[0097] The electrolyte, positive electrode sheet, negative electrode sheet and isolation film (PE film) obtained in the embodiment and the comparative example are processed into a battery with a thickness of 8 mm, a width of 60 mm and a length of 130 mm through a lamination process, and vacuum baked at 85°C for 10 h, injected with electrolyte, and left to stand for 24 h. Thereafter, the battery is charged to 4.2 V with a constant current of 0.1C (200 mA), and then charged to 0.05C (100 mA) with a constant voltage of 4.2 V, and then discharged to 2.8 V with a constant current of 0.1C (200 mA) (the discharge capacity C0 is recorded here as the capacity of the battery), and the charge and discharge are repeated twice. Finally, the battery is charged to 3.65 V with a constant current of 0.1C (200 mA) to obtain a lithium ion battery.

[0098] The specific results are shown in Table 2.

[0099] Table 2

[0100] Battery capacity C0 (mAh) Example 1 2004 Example 2 1995 Example 3 2005 Example 4 2009 Example 5 1992 Example 6 1991 Example 7 2003 Comparative Example 1 1972 Comparative Example 2 1975 Comparative Example 3 1962

[0101] It can be seen from the data in Table 1 and Table 2 that the lower the shear viscosity of the embodiment of the present invention, the better the fluidity, and at the same time, the embodiment has excellent capacity performance.

[0102] Comparing Example 1 with Comparative Example 3, it can be seen that although Comparative Example 3 using oxalic acid still maintains good fluidity, the oxalic acid will generate water when neutralizing the residual alkali, resulting in a decrease in battery capacity and failing to meet actual needs.

[0103] By comparing Example 1 with Example 4, it can be seen that when tert-butyl-p-hydroxyanisole and 2,6-di-tert-butyl-p-benzophenol are used at the same time, the flow characteristics of the slurry can be further improved and the capacity of the battery can be increased.

[0104] By comparing Example 1 with Example 6, it can be seen that there is a synergistic effect between the first conductive agent and the second conductive agent in the present invention, which can improve the fluidity and stability of the slurry and increase the capacity of the positive electrode material.

[0105] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A slurry of high nickel positive electrode active material, characterized in that: The slurry includes a solid component and a solvent, and includes the following components in percentage by weight based on the total weight of the solid component: High nickel positive electrode active material 94%-98.5%; Antioxidants 0.005%-0.5%; Halogenated silane 0.01%-0.5%; Polyvinylidene fluoride 1%-2%; Conductive agent 0.5%-3%.

2. The slurry according to claim 1, characterized in that The antioxidant includes at least one of butylated p-hydroxyanisole, 2,6-di-tert-butyl-p-quinone, propyl gallate, tert-butylhydroquinone, and benzoquinone; Optionally, the antioxidant includes butylated hydroxyanisole and / or 2,6-di-tert-butylated hydroxybenzool; Optionally, the halogenated silane includes silicon tetrachloride and / or hexachlorodisilane.

3. The slurry according to claim 1 or 2, characterized in that The conductive agent includes at least one of conductive carbon black, conductive graphite, carbon fiber, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; Optionally, the conductive agent includes a first conductive agent and a second conductive agent; The first conductive agent includes at least one of conductive carbon black, conductive graphite, and carbon fiber; The second conductive agent includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; And / or, based on the total solid mass percentage in the slurry of high-nickel positive electrode active material, the amount of the first conductive agent is 1%-2%, and the amount of the second conductive agent is 0.2%-0.8%.

4. The slurry according to claim 1, characterized in that The high-nickel cathode active material includes at least one of high-nickel ternary cathode material, cobalt-free cathode material, and quaternary cathode material; the composition of the high-nickel ternary cathode material is LiNi x Co y Mn 1-x-y O2, where 0.7 ≤ x < 1, 0 < y ≤ 0.3, 0 < x + y < 1; the composition of the cobalt-free cathode material is LiNi x Mn 1-x O2, where 0.7 ≤ x < 1; the composition of the quaternary cathode material is LiNi x Co y Mn z Al 1-x-y-z O2, where 0 < x + y + z < 1.

5. The slurry according to claim 1, characterized in that The number average molecular weight of the polyvinylidene fluoride is 500,000-1.5 million; And / or, the mass ratio of the solvent to the polyvinylidene fluoride is (90-100):(1-10); And / or, the solvent comprises at least one of N-methylpyrrolidone, N-ethylpyrrolidone and dimethyl sulfoxide, preferably N-methylpyrrolidone.

6. A method for preparing the slurry according to any one of claims 1 to 5, characterized in that: The high-nickel positive electrode active material, antioxidant, halogenated silane, polyvinylidene fluoride and conductive agent are mixed to obtain a slurry of the high-nickel positive electrode active material.

7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: S1, first mixing polyvinylidene fluoride and a solvent to obtain a glue solution; S2, performing a second mixing of the above-mentioned glue solution, conductive agent, and high-nickel positive electrode active material to obtain a mixture; S3, performing a third mixing of the mixture, the antioxidant, and silicon tetrachloride to obtain a slurry of high-nickel positive electrode active material.

8. The preparation method according to claim 7, characterized in that: In step S2, the first conductive agent is mixed with the glue solution to obtain conductive glue A, and the second conductive agent is added and mixed to obtain conductive glue B; and the conductive glue is then mixed with the high-nickel positive electrode active material to obtain a mixture.

9. A secondary battery, characterized in that: The battery comprises a slurry of a high-nickel positive electrode active material according to any one of claims 1 to 5.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Positive electrode for secondary battery, and secondary battery

    CN104137311A

  • Battery

    CN104733787A

  • Carbon-coated high nickel ternary positive electrode material and preparation method therefor

    CN108878828A

  • Electrolyte for lithium-air battery or lithium-lithium symmetric battery

    CN111200161A

  • Doped and coated single crystal positive electrode material and method for doping and coating single crystal positive electrode material

    CN111697221A